Alcohol Use Disorder: The Main Role of Nursing Interventions Protocols and The Critical Roles of Healthcare Security Workers-An Updated Review - Al-Mutairi, Turki Wasmi; Alharbi, Talal Awadh; Alrumaykhani, Abdulaziz Ali; Alsharari, Mamdouh Marzouq Muaysh; Al-Sharari, Abdulaziz Obaidullah Zayed; Alyhya, Abdullah Abdulaziz Mohammed; Alotaibi, Sultan Faihan; Alshahrani, Day Muhamad Falih; Alshahrani, Dhafer Saeed; Alotaibi , Athari Batea; Alnefaie, Salem Fahad Abdullah (Journal of Ecohumanism, 2024)
Background: Alcohol Use Disorder (AUD) is a widespread public health concern with significant social, economic, and health implications. In the U.S., approximately 5.9% of individuals aged 12 and older meet the criteria for AUD, with alcohol misuse linked to various mental health, physiological, and social issues. Studies reveal that AUD often coexists with other health conditions like poor nutrition, mental disorders, and diminished performance in occupational or academic settings. The severity of AUD demands effective nursing interventions and healthcare security workers’ involvement, especially in acute clinical settings. Aim: The aim of this review is to examine the role of nursing interventions and healthcare security workers in the management of Alcohol Use Disorder, focusing on the integration of care approaches and the critical role security workers play in preventing harm and facilitating timely medical interventions. Methods: This review systematically synthesizes current literature on AUD, highlighting nursing management protocols, healthcare security workers’ roles, and the challenges associated with managing patients with alcohol use disorders in various healthcare settings. Relevant studies were reviewed to present evidence on the efficacy of nursing interventions, and the involvement of security staff in patient safety and care delivery. Results: Nursing interventions, such as the use of motivational interviewing and cognitive-behavioral therapy (CBT), have been shown to aid in the management and treatment of AUD. Security workers play an essential role in identifying critical situations, such as alcohol intoxication, withdrawal, or aggression. Their ability to assess sudden mood changes, unresponsiveness, confusion, and unstable vital signs is vital in ensuring that individuals with AUD receive timely medical care. Effective collaboration between healthcare teams and security personnel can lead to improved patient outcomes. Conclusion: Addressing alcohol use disorder requires a comprehensive, multifaceted approach that incorporates both nursing interventions and the critical roles of healthcare security workers. Security staff are integral to identifying patients at risk and ensuring that they receive appropriate medical attention. Ongoing training for security workers in recognizing alcohol misuse signs and de-escalating aggressive behaviors is crucial for improving patient safety and care quality